Displacing, squeezing, and ramming: The role of nuclear lamins in leukocyte migration. Issue 2 (2nd May 2018) - Marelli‐Berg, Federica M.; Nadkarni, Suchita
Abstract : Discussion on the role of lamin A and nuclear deformability in granulocyte migration though endothelial and matrix barriers.